Development of Learning Tools for Mathematics Content Based on a Contextual Approach to Improve the Higher-Level Thinking Ability of 5th Grade SDN Students 047179 Kutagerat - Melina Br. Sembiring; Mulyono Mulyono; Zulkifli Matondang (Budapest International Research and Critics University, 2021)
This research aims to knowing the validity of learning tools developed using a contextual approach in improving the high-order thinking skills of students of SDN 047179 Kutagerat; know the practicality of the learning tools being developed; know the effectiveness of learning tools; and knowing the increase in students' higher order thinking skills using learning tools based on a contextual approach. This study uses the Thiagarajan 4-D development model. VaThe lidity of learning media used descriptive statistical analysis. Data analysis to find out how the increase in the score of increasing student learning outcomes can be obtained from the normalized gain index data. The results showed that: (1) The results of the validator's assessment of the four mathematics learning tools based on the contextual approach that had been developed were as follows: (a) the linguist's assessment obtained an overall average of 93%; (b) the design expert's assessment obtained an overall average of 93.13%; (c) the material expert's assessment obtained an overall average of 96%. The results of the validation of the four learning tools by the validator are in the criteria of